Domestic cash flow and credit management: knowledge, behaviour and practice among the Kedah state government servants in the district Kuala Muda / Siti Salmah Abu Bakar ... [et al.] - Abu Bakar, Siti Salmah; Wan Abdullah, Wan Faizah; Abdul Rahim, Noraini; Ismail, Jurina (2011)
Money, being an essentials needs, place a vital role in a human life. Therefore , good knowledge on financial management is important to individuals, families and the community at large so that they can achieve their financial objectives such as living within their financial means and increasing their financial security . Current knowledge of domestic cash flow and credit management is scarce . According to Godwin and Carroll (1986) little research has focused on financial management attitude and behaviour of families . Moreover, Malaysia is lack of published local literature on the area of cash management particularly domestic practice . Most of the literature focused on the spending pattern. According to Godwin and Koonce (1992), family financial management is the planning, implementing and evaluating behaviour of families involved in allocating the family's flow of income toward meeting their financial goals . A study by Hilgert, Hogarth and Beverly (2003) on household financial management practices found that financial knowledge can be statistically linked to financial practices related to cash flow management, credit management, savings and investment. Research done by Jinhee and Garman (2003) found that workplace financial education, combined with individual financial counselling advice session, have some positive effects on workers financial attitudes and behaviours for U.S. employees .